2014
DOI: 10.1002/hlca.201300378
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel α‐(Acyloxy)‐α‐(quinolin‐4‐yl)acetamides by a Three‐Component Reaction between an Isocyanide, Quinoline‐4‐carbaldehyde, and Arenecarboxylic Acids

Abstract: Novel α‐(acyloxy)‐α‐(quinolin‐4‐yl)acetamides were synthesized by the Passerini three‐component reaction between an isocyanide, quinoline‐4‐carbaldehyde, and arenecarboxylic acids in H2O. The reactions were carried out in one pot at room temperature with quantitative yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The organic segment is connected to the isocyanide group via the nitrogen atom, not via the carbon. They are used as privileged synthons for the synthesis of other organic compounds in particular various heterocycles [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , frequently via multicomponent reactions (MCRs) namely isocyanide multicomponent reactions (IMCRs) 25,[38][39][40][41][42][43][44][45][46][47][48][49] . Noticeably isocyanides are susceptible to polymerization 50 .…”
Section: Introductionmentioning
confidence: 99%
“…The organic segment is connected to the isocyanide group via the nitrogen atom, not via the carbon. They are used as privileged synthons for the synthesis of other organic compounds in particular various heterocycles [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , frequently via multicomponent reactions (MCRs) namely isocyanide multicomponent reactions (IMCRs) 25,[38][39][40][41][42][43][44][45][46][47][48][49] . Noticeably isocyanides are susceptible to polymerization 50 .…”
Section: Introductionmentioning
confidence: 99%
“… 25 It has been hypothesized that the reaction can proceed either via an “open chain” mechanism (where the key intermediates is a nitrilium ion) or via a “concerted mechanism” (where an intermediate nitrilium ion is not formed; Scheme 4 ). In polar solvents such as methanol or water, the reaction should proceed with an “open chain mechanism” 26 via protonation of the carbonyl component followed by nucleophilic addition of the isocyanide and carboxylate residue, respectively. The resultant intermediate undergoes acyl group transfer to give the α-acyloxyamide.…”
Section: Resultsmentioning
confidence: 99%
“…For example, U-MCR was used by Merck as a route to the anti-HIV drug Crixivan (Rossen et al, 1998 ). Even though these reactions are usually conducted in organic solvents (Neyer et al, 1990 ; Qu et al, 2011 ), there are several reports on using aqueous media as a solvent (Pirrung and Sarma, 2004 ; Vessally et al, 2011 ; Taran et al, 2014 ). We have shown that the addition of dioctadecyldimethylammonium bromide (DODAB), a cationic vesicle forming surfactant, noticeably improves the course of the Passerini reaction in aqueous solution leading to corresponding α-acyloxycarboxamides 8 with higher yields than under standard conditions in dichloromethane or water (Paprocki et al, 2015 ).…”
Section: Isocyanide-based Multicomponent Reactionsmentioning
confidence: 99%